PENERAPAN GAME EDUKATIF UNTUK MEMFASILITASI PERKEMBANGAN LITERASI ANAK PENDERITA DYSLEXIA PADA SEKOLAH DASAR DENGAN MENGGUNAKAN CONSTRUCT 2 - Dzakirah , Nasya Rabbi; Zaliluddin, Dadan (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2025)
This study investigates how using Construct 2-based educational games as interactive learning tools can help children with dyslexia develop their literacy skills in elementary school. More engaging and tailored learning media are needed because they often experience difficulties in reading, recognizing letters, and understanding text. To increase student engagement in the learning process, educational games have interactive visual displays, supporting sounds, and simple gameplay. The research methods used were design, development, and testing on students with dyslexia. The results showed that the use of this educational game can increase students' interest in learning, improve their ability to understand letters and words, and make the learning process enjoyable. Therefore, Construct 2-based educational games can be an alternative learning tool that is useful for supporting the literacy development of children diagnosed with dyslexia in elementary school.